The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jerd.12270
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Prospective Clinical Evaluation of Monolithic and Partially Veneered Zirconia Single Crowns

Abstract: During the observation time, both monolithic and partially veneered zirconia crowns showed an outstanding low technical complication rate: only one minor chipping and three losses of retention were observed. Additionally, esthetics was excellent. Based on these results the clinical use of this kind of restoration is promising. (J Esthet Restor Dent 29:22-30, 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
47
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 23 publications
(58 reference statements)
13
47
0
10
Order By: Relevance
“…Bomicke et al evaluated clinical performance and esthetics of monolithic and partially veneered zirconia single crowns for a 3‐year period and found that complications were predominantly biological in nature. The 3‐year failure‐free survival rate was 98.5% for both MZ and veneered zirconia . These results are consistent with the results of the present study where the survival rate was 100%, and the results could be classified as “Excellent” over a 1‐year follow up.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Bomicke et al evaluated clinical performance and esthetics of monolithic and partially veneered zirconia single crowns for a 3‐year period and found that complications were predominantly biological in nature. The 3‐year failure‐free survival rate was 98.5% for both MZ and veneered zirconia . These results are consistent with the results of the present study where the survival rate was 100%, and the results could be classified as “Excellent” over a 1‐year follow up.…”
Section: Discussionsupporting
confidence: 91%
“…Although MZ is a popular restorative material, there are only a few clinical studies on survival of MZ crowns and wear of the antagonistic natural teeth . Since laboratory studies do not accurately simulate clinical performance, the final test of a material will always be its performance in the mouth.…”
mentioning
confidence: 99%
“…Thus, this type of treatment is considered as promising, but clinical studies with longer follow-up times are still desirable. 21 Another study collected data over five years from two United States laboratories. The laboratories provided insurance for restorations of monolithic zirconia that had problems, making new restorations without additional costs to the clinicians.…”
Section: Monolithic Zirconia Restorationsmentioning
confidence: 99%
“…Zirconia ceramics have presented the best mechanical properties among the ceramics . Two main zirconia restoration categories include zirconia‐based and monolithic zirconia restorations . Monolithic zirconia restorations, which are prepared with only zirconia ceramics, have some advantages over zirconia‐based restorations, such as no need for layering and a simpler and shorter CAD/CAM process .…”
mentioning
confidence: 99%